Long-term study of the intermittent extreme behaviour of 1ES 2344+514 - A. Arbet-Engels; H. A. Mondal; S. Fukami; F. D’Ammando; D. Dorner; R. Chatterjee; P. Majumdar; M. Manganaro; T. Hovatta; M. Villata; M. Perri; F. Verrechia; et al. (Italy, 2026)
Extreme high-frequency-peaked BL Lac objects (EHBLs) are the most energetic persistent sources in the Universe. They are characterized by a spectral energy distribution (SED) featuring a synchrotron peak energy above 1 keV. 1ES 2344+514 is a blazar known to behave as an EHBL intermittently. Until now, its EHBL nature was only reported during flares, but a coherent picture is missing as unbiased monitoring campaigns are lacking. This work presents the longest observing campaign from radio to very-high-energy (VHE) frequencies performed so far on 1ES2344+514. Using observations during 2019-2021, we carry out a systematic investigation of the intermittent EHBL phases. Together with MAGIC, the dataset also includes X-ray observations from NuSTAR, XMM-Newton, and AstroSAT, providing an unprecedented determination of the two SED components. For the first time we report a clear EHBL behaviour during a low flux activity in 1ES 2344+514. It implies a significant hardening of the electron distribution inside the jet independent of flux. We also detect a bright X-ray state characterized by an unusually soft spectra, thus violating the harder-when-brighter relation typically found in blazars. The SED study further reveals an excess in the ultraviolet data with respect to the extrapolation of the X-ray spectrum, suggesting at least two regions contributing to the synchrotron flux. Finally we investigate a gamma-ray flare not accompanied by an X-ray counterpart. This peculiar outburst is interpreted using a time-dependent model involving two emitting components.